Crow girl - Cann, Kate. (Edinburgh : Stoke Books, 2012)
Lilly finds self-confidence and the strength to stand-up to a bully through her friendship with crows.
2.9
Young Adult.
Young Adult
Keywords: Crows -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Crows -- Fiction; Human-animal relationships -- Fiction; Self-acceptance -- Fiction; Crows -- Fiction; Human-animal relationship -- Fiction; Self-acceptance -- Fiction